2011
DOI: 10.1093/mutage/ger032
|View full text |Cite
|
Sign up to set email alerts
|

The association between MLH1 -93 G>A polymorphism of DNA mismatch repair and cancer susceptibility: a meta-analysis

Abstract: DNA mismatch repair, known as a fundamentally biological pathway, plays key roles in maintaining genomic stability, eliminating mismatch bases and preventing both mutagenesis in the short term and cancerogenesis in the long term. Polymorphisms of MLH1 in individuals may have an effect on the DNA repair capacity and therefore on cancer risk. Recently, emerging studies have been done to evaluate the association between MLH1 -93 G/A polymorphism and cancer risk in diverse populations. However, the results remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…The finding that there was no statistically significant relationship between MLH1 À93G>A polymorphism and the total number of colorectal tumours is in line with previously published meta-analyses [7,9]. Nevertheless, the aim of our study was to analyse whether this polymorphism is associated with familial colorectal cancer which complied with the Amsterdam or Bethesda criteria, or whether it was related to sporadic colorectal cancer.…”
Section: Discussionsupporting
confidence: 82%
“…The finding that there was no statistically significant relationship between MLH1 À93G>A polymorphism and the total number of colorectal tumours is in line with previously published meta-analyses [7,9]. Nevertheless, the aim of our study was to analyse whether this polymorphism is associated with familial colorectal cancer which complied with the Amsterdam or Bethesda criteria, or whether it was related to sporadic colorectal cancer.…”
Section: Discussionsupporting
confidence: 82%
“…In a recent meta-analysis study, no association with CRC was observed (Pan et al, 2011). However, Allan et al (2008) reported that MLH1 -93A was associated with a 3-fold increased risk of CRC, negative for the MLH1 protein detectable by immunohistochemistry (OR = 3.30, 95%CI = 1.46-7.47), while Raptis et al (2007) documented a 3-fold increased risk (P < 0.001) of CRC with MSI-H (microsatellite instability high) in a population from Ontario (OR = 3.23, 95%CI = 1.65-6.30) and an 8-fold increased risk (P < 0.001) in Newfoundland people (OR = 8.88, 95%CI = 2.33-33.9).…”
Section: Discussionmentioning
confidence: 91%
“…Although three similar meta-analyses have reported the existence of an association between the MLH1 -93G>A polymorphism and the risk of CRC [22], [28], [29], they showed some different results. For instance, Whiffin et al reported the pooled effect on the -93G>A polymorphism and CRC based on five case-control studies with a total of 14,121 CRC cases and 10,890 controls [22].…”
Section: Discussionmentioning
confidence: 97%